Ethnomedicinal Investigation of Medicinal Plants of Chakrata Region (Uttarakhand) Used in the Traditional Medicine for Diabetes by Jaunsari Tribe - Kumar, Ankit (Nat Prod Bioprospect, 2019)
The Himalayan region is the treasure house of natural wealth, particularly of medicinal and aromatic plants. These plants are used by the Indian traditional healers for the past many centuries to treat various ailments such as skin disorders, asthma, diabetes, snake bite, fever, pain, eye diseases, diarrhoea, indigestion, jaundice, burn, wound, liver disorder, CNS disorders and urinary tract infection. The indigenous traditional knowledge of medicinal plants and therapies of various local communities has been lost due to changes in traditional culture and the introduction of modern technologies. Therefore, it is essential to explore the traditional knowledge of the indigenous medicinal plants mainly in such areas where there is a severe threat to natural vegetation owing to human inhabitation. The present study aimed to explore the medicinal plants of Chakrata region (Jaunsar–Bawar Hills), Uttarakhand, India used in the folk medicine for the management of diabetes by Jaunsari Tribe. In a comprehensive field survey, the information about the medicinal plants have been mainly collected from the traditional healers and other elderly people belong to the tribal community. All the information about the medicinal plants of the study area was documented in a field book. Various tools have been used to collect the samples for identification purpose and the authentication of the plants was done with the help of taxonomists. The literature on these plants was also searched from online (PubMed and Scopus) as well as from some textbooks and Ayurvedic classical texts. The present survey-based work described a total of 54 plants belonging to 47 genera and 30 families used in the traditional medicine for the management of diabetes in Chakrata region. The information gathered from the local community revealed that the plants are effective in diabetes and one can use most of them without consulting a practitioner or traditional healer. The literature revealed that most of the surveyed plants are already used in the preparation of various antidiabetic formulations such as Chandraprabha vati, Nishamalaki chunra, Amritamehari churna and Nisakathakadi kashayam along with various patent drugs which are frequently prescribed by the Ayurvedic practitioners in India. The present study explored the traditional as well as scientific knowledge on the antidiabetic plants used by the tribal community. The documented information on these plants can be further used by the scientific community to develop new drugs/formulations with the help of modern techniques.